2018
DOI: 10.1051/epjconf/201818302034
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Technique for Dynamic Fragmentation of Liquid-Driving Expanding Ring

Abstract: Expanding ring experiment is an important method for dynamic fragmentation of solid under 1D tensile loading. Based on the split Hokinson pressure bar (SHPB), a liquid-driving experimental technology was developed for conducting expanding ring tests. The loading fixture includes a hydraulic cylinder filled with water, which is pushed by a piston connected to the input bar. As the water is driven, it expands the metallic ring specimen in the radial direction. The approximately incompressible property of the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Expanding ring experiments are a well-established technique for studying the dynamic fragmentation of metals [13][14][15][18][19][20][21][22][23][24] , which have been applied, though much less frequently, to ceramics 20 , plastics 25 , but not geological materials. Similar experiments (cylinders rather than rings) are also used to examine similar material behaviour for example 26,27 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Expanding ring experiments are a well-established technique for studying the dynamic fragmentation of metals [13][14][15][18][19][20][21][22][23][24] , which have been applied, though much less frequently, to ceramics 20 , plastics 25 , but not geological materials. Similar experiments (cylinders rather than rings) are also used to examine similar material behaviour for example 26,27 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Moreover, during the fragmentation, electric arcs were generated at rupture points that modified the local surface appearance. Then, Zhang et al [9] used a modified split Hopkinson pressure bar (SHPB) set-up to put water under pressure and expand a ring at strain rate up to 10 3 s -1 . This set-up enabled a good observation of the experiment and was shown repeatable.…”
Section: Introductionmentioning
confidence: 99%
“…( 10) that need to be determined, the explosion period t d − t e , the ratedependent strength σ * (ε) and k 2 G h . Kahana et al 9 and Zhang et al 10,11 conducted ring expansion tests of AZ31 magnesium alloy rings (r = 16.3mm, h = 1.7mm, E = 45GPa, v = 0.35, σ * = 240MPa, ρ = 1.8Kg m 3 ) and 1060 aluminum rings (r = 16mm, h = 1.5mm, E = 72GPa, v = 0.33, σ * = 90MPa, ρ = 2.68Kg m 3 ) respectively. For the test of AZ31 magnesium alloy rings 9 , the load increased from zero to a certain value over a very short period of time and the ring finally segmented in about 20µs.…”
mentioning
confidence: 98%
“…a) chshshen@nwpu.edu.cn b) Corresponding Author: chaozhang@nwpu.edu.cn Zhang and Ravi-Chandar 7,8 revealed that the onset of fragmentation is caused by the development of a part of the nucleated necks, thus the number of necks formed exceeds the number of fragments, and the variance of the fragment length decreases with the increase of the expanding velocity suggesting its value becomes zero when the expanding velocity is sufficiently high. More recently, both experiments [9][10][11][12] and finite element simulations 13,14 have shown that defects barely affect the average neck spacing and the neck spacing no long reduces at very high expanding velocity, which could not be explained by the statistical fragmentation theory of Mott. Thus it has raised the question that the localization process become deterministic at high expansion velocities.…”
mentioning
confidence: 99%